História das práticas de diversão em Cataguases - MG: indícios a partir do Jornal Cataguazes (1906 a 1930) - Priscila Gonçalves Soares (2021)
This investigation sought to portray the entertainment practices that took place between 1906 and 1930 in the city of Cataguases - MG, for the realization of this thesis, the newspaper Cataguazes, official organ of the local government, was used as a primary source. The theoretical bases of Cultural History underpinned the dialogues established between sources and scientific literature. Through the documentary analysis of newspapers, it was possible to see that the entertainment practices disclosed were part of a movement of the local elite interested in placing the city at the modernist, progressive and civilized vanguard of the time. To this end, the entertainment practices found in newspapers revealed changes in the habits of the people of Cataguases and a journalistic clamor that influenced collective thinking according to educational interests, class and gender. The newspaper defended normative values that conjectured with the local norm to be established, in this way, the attendance to the circuses started to be frowned upon and the theater the adequate entertainment due to its educational and civilizing character; theater and cinema shared the same space, in alternating moments they represented education and progress in Santa Catarina, while Humberto Mauro produced the first national films in the city, modern sports indicated the future paths and reified gender issues. The practice of basketball by women, on the one hand, signaled the advance of times with the conquest of the right to practice sports, on the other, the permanence of beauty, delicacy and long skirts. Metaphorically, the physical capacity, brutality and strength were in charge of the men with the practice of soccer in the fields of floodplains and in the streets of the city, influencing the city dynamics, spreading dust through the urb. Associations were created and these gave rise to football clubs such as Flamengo and Operario, spaces that mixed fun and work, rivalries expressed by the sport. No other entertainment seems to have changed the dynamics of the city such as football, the attendance of the public, transport logistics, the creation of spaces for practice, the chartering of trains for sporting excursions, uniforms made up of shorts (as women they remained with the long skirts), the relationships with the body, with the language and the cultural transit that occurred in a sneaky way. The market for entertainment was also boosted by sports and competitions often held, local businessmen started to invest in this business and at the end of the 20s they founded an elite club in the city that would offer sports such as basketball, soccer, rowing, gymnastics, volleyball, swimming, tennis, skating and sailing. It was observed that the entertainment practices disclosed, most of the time, were related to the urban elite, the participation of different social strata was made invisible in the newspaper, limitations of the source used for the research, newspaper Cataguazes, a fact that instigates new research in favor of to identify the silencing around other entertainment practices that occurred in the city and were not reported by the newspaper Cataguazes, a challenge that will remain for a future investment.